2017
DOI: 10.5489/cuaj.4279
|View full text |Cite
|
Sign up to set email alerts
|

Chronic prostatitis/chronic pelvic pain syndrome is associated with previous colonoscopy

Abstract: Introduction: This study aimed to examine the association between chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) and receipt of a prior colonoscopic examination using a populationbased database. Methods: We used the Taiwan Longitudinal Health Insurance Database 2005 to retrieve the study sample. This study included 3933 patients with CP/CPPS and 3933 age-matched controls. We designated the date of receiving the first diagnosis of CP/CPPS as the index date for cases. We defined the first an ambulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Although there are no reports of bacterial prostatitis occurring acutely after colonoscopy Tsai et al have reported an association between antecedent colonoscopy and chronic prostatitis/chronic pelvic pain syndrome. 3 The standard for diagnosing acute bacterial prostatitis (ABP) relies on the finding of bacteria within prostatic fluid. However, techniques to express prostatic fluid can be difficult to carry out and are hardly performed in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are no reports of bacterial prostatitis occurring acutely after colonoscopy Tsai et al have reported an association between antecedent colonoscopy and chronic prostatitis/chronic pelvic pain syndrome. 3 The standard for diagnosing acute bacterial prostatitis (ABP) relies on the finding of bacteria within prostatic fluid. However, techniques to express prostatic fluid can be difficult to carry out and are hardly performed in clinical practice.…”
Section: Introductionmentioning
confidence: 99%